Aural and nasal anthropometry: An observational study - Pratima Jaiswal; Aastha Sharma; Aarushi Jain (Wolters Kluwer Medknow Publications, 2022)
Background: Neoclassical analysis of the human face is based on assumptions that certain fixed ratios exist between parameters of a harmonious face, these relationships of the human face have been called canons. One of the facial canons is nasoaural proportion canon most commonly followed for facial reconstructive surgeries. This study aimed to determine the applicability of nasoaural proportion and inclination canon in the participants and to explore the sexual dimorphism of nasoaural parameters among them. Methodology: This observational study was performed in the department of anatomy from May 2018 to May 2019. The study participants aged from 18 to 25 years of which 50 were male and 50 were female. Nose height and ear height were measured by a digital vernier caliper. Nasofacial angle and ear angle were measured using a goniometer. All the parametric data were analyzed by t-test using MedCalc software. Results: Classical nasoaural facial canon was followed by only one (male) participant while none of the males and females followed the classical nasoaural canon. The average ratio of nose height to ear height was 0.7 in both genders. Nasoaural canon showed that nasal height and ear height were fairly correlated. The inclination canon was followed by 18% males and 8% females only. Conclusion: The ideal neoclassical canons did not seem to apply to our sample when measurements were implemented. Therefore, these cannot prove a useful basis of modus operandi in achieving esthetic goals in the Indian population.